Pengaruh Croscarmellose Sodium Terhadap Mutu Fisik Orally Disintegrating Tablet Glibenklamid Hasil Dispersi Padat - Hariyani, Bunga Fitri; Harjanti, Reslely; Priyanto, Widodo (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Glibenclamide is the second generation of the sulfonylurea group, which is used orally in patients with type 2 diabetes mellitus. Oral tablet preparations are still the main choice because they have the exact size of the usual desired dose, whereas for liquid preparations, patients must measure the medicine themselves. Pediatric and geriatric patients generally often experience difficulties when swallowing tablet or oral medications. So, to overcome this, an ODT preparation was made, the way to consume it is just to put it on the tongue, then the ODT tablet will disintegrate and dissolve in saliva. The aim of this research was to determine the variation of croscarmellose sodium that produces the best physical quality of Glibenclamide ODT tablets. The manufacture of Glibenclamide ODT has been carried out using the mixture method (dissolution-mixing). The solid dispersion that has been used is PEG 4000 and uses various concentrations of Croscarmellose Sodium, namely 0 mg, 2 mg, 4 mg, 6 mg, and 8 mg. The resulting ODT tablets were evaluated using several parameters, namely hardness test, friability test, wetting test, in vitro disintegration time test, and taste response test. The data obtained will be analyzed using one-way ANOVA with a confidence level of 95%. Research results have shown that the use of 4% Croscarmellose Sodium has resulted in the fastest in vitro disintegration (disintegration) time of 4.44 seconds, and the fastest wetting time of 21.67 seconds. The higher the concentration of croscarmellose sodium can produce the best physical quality.